2009
DOI: 10.1002/mren.200800030
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Optimization Approach to Optimal Production Scheduling in an Industrial Continuous Olefin Polymerization Reactor

Abstract: The time‐optimal grade‐transition policies, as well as the selection of the optimal grade production sequence, are calculated for a gas‐phase ethylene/but‐1‐ene copolymerization FBR. The tuning parameters (i.e., proportional gain and integral time) of the feedback PI process controllers, as well as the time‐optimal trajectories of the feedforward controllers, are treated as decision variables. A two‐level decomposition approach is applied for solving the optimal‐grade transition‐scheduling problem, taking into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…For the quality variable of cumulative melt index MI c (t), it can be described as (1) in which MI i (t) is the instantaneous melt index and parameter τ MI is decided by the inflow and outflow rates. For the quality variable of cumulative density ρ c (t), it can be described as the similar form of…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For the quality variable of cumulative melt index MI c (t), it can be described as (1) in which MI i (t) is the instantaneous melt index and parameter τ MI is decided by the inflow and outflow rates. For the quality variable of cumulative density ρ c (t), it can be described as the similar form of…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…1 Therefore, accurate dynamic models of the crucial quality variables are important for process control. Because most processes involve a mixing stage, the corresponding indices, such as melt index, density, and molecular weight, perform cumulative characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Chatzidoukas et al demonstrated the economic benefit of implementing scheduling in a MIDO problem for polymerization, solving product grade transitions along with the scheduling problem [22]. Economic benefit has also been shown for simultaneous selection of linear controllers for grade transitions and scheduling, ensuring that the process dynamics from the controller selection are accounted for in the scheduling problem [23]. Terrazas-Moreno et al also demonstrate the benefits of process dynamics in cyclic scheduling for continuous chemical processes [45].…”
Section: Previous Workmentioning
confidence: 99%
“…Chatzidoukas et al study solving the simultaneous dynamic optimization optimal grade transitions and scheduling problem for fluidized-bed reactors (FBR) via a MIDO approach with orthogonal collocation on finite elements [35]. They also study simultaneous selection of closed-loop controllers and selection of controller parameters with the scheduling problem for polymerization processes [36,37]. Terrazas-Moreno and Flores-Tlacuahuac also investigate simultaneous cyclic scheduling and control of continuous chemical processes, and study a langrangean heuristic method for reduction of computational burden [15,18].…”
Section: Literature Reviewmentioning
confidence: 99%